From the disappearance of the Roman pottery to the shattered identity in the post-modernity: some remarks on the concept of identity in the Roman Archaeology - Silva,António oJoséMarquesda (Romanitas - Revista de Estudos Grecolatinos, 2016)
In the last two decades, the studies of Roman archaeology witnessed a major conceptual shift. During this period we assisted to a gradual decline of the use of the old concept of ‘Romanization’ following the rejection of the epistemological premises that it carried out. Simultaneously, we have seen an increasingly frequent use of the concept of identity and the replacement of the concept of ‘Romanization’ by a form of Roman cultural identity spreading, understood by an analogy with the process of globalization that defines the post-modern world we live on. Currently, it seems difficult to write about the Roman culture without using the word identity. We can read, often in the same text, an author telling us about Roman identity, imperial identity, native identity, ethnic identity, local identity, cultural identity, spiritual identity or self-identity and the relation between these fragmented identities with the material culture in Roman times. As such, the polysemous application of this concept in Roman archaeology must be understood in the light of its transdisciplinary use among social sciences and as the common language notion in everyday life. In this communication we propose to address how the post-modern understanding of the concept of identity affects the ways we approach material culture in Roman archaeology and to discuss if the concept can really help us to understand how people categorize themselves in Roman times.